The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-46149-0
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil treatment modulates functional connectivity in stroke survivors with severe fatigue

Abstract: Post-stroke fatigue has a significant impact on stroke survivors’ mental and physical well-being. Our recent clinical trial showed significant reduction of post-stroke fatigue with modafinil treatment, however functional connectivity changes in response to modafinil have not yet been explored in stroke survivors with post-stroke fatigue. Twenty-eight participants (multidimensional fatigue inventory-20 ≥ 60) had MRI scans at baseline, and during modafinil and placebo treatment. Resting-state functional MRI data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…However, Iidaka et al have shown evidence that this network is also associated with successful retrieval in episodic memory (Iidaka et al, 2006 ). FC within the FPN has been shown to be modulated by different stimulants such as MOD (Esposito et al, 2012 ; Visser et al, 2019 ); CAF (Haller et al, 2013 ; Koppelstaetter et al, 2008 ) and MPH (Mehta et al, 2000 ; Mueller et al, 2014 ). In fact, Schmidt and colleagues report a broad recruitment of frontoparietal regions when MOD and MPH are consumed compared with placebo (Schmidt et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Iidaka et al have shown evidence that this network is also associated with successful retrieval in episodic memory (Iidaka et al, 2006 ). FC within the FPN has been shown to be modulated by different stimulants such as MOD (Esposito et al, 2012 ; Visser et al, 2019 ); CAF (Haller et al, 2013 ; Koppelstaetter et al, 2008 ) and MPH (Mehta et al, 2000 ; Mueller et al, 2014 ). In fact, Schmidt and colleagues report a broad recruitment of frontoparietal regions when MOD and MPH are consumed compared with placebo (Schmidt et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…38 A third small study (n = 12) used fMRI to show that reduced network functional connectivity in the ipsilesional rostral middle frontal cortex was associated with higher fatigue severity. 52 Two studies assessed the effect of modafinil on fMRI functional connectivity (FC) in PSF, 55,56 using data from the double-blind MIDAS-II trial (n = 36), which showed modafinil 200 mg daily reduced PSF compared to placebo. 62 In a subgroup of 28 who had fMRI, modafinil treatment was associated with increased resting-state functional connectivity (rsFC) in the right hippocampus compared to placebo, and lower rsFC in the left frontoparietal, somatosensory, and mesolimbic network.…”
Section: Number Of Infarctsmentioning
confidence: 99%
“…The MFI-20 has been validated and/or used in several clinical and healthy populations since 1995, including patients with neurological diseases, e.g. multiple sclerosis, stroke, polio and spinal muscular atrophy [19][20][21][22][23][24][25]. The MFI-20 was in 2000, in a study of fatigue in the Danish background population, validated and translated into Danish [26,27].…”
Section: Fatiguementioning
confidence: 99%